The ethological concept of animal and human behaviour. An attempt at methodological analysis - Kośmicki, Eugeniusz (Anthropological Review, 1980)
The paper presents a methodological analysis of the structure of the ethological theory aimed at explanation of behaviour. Ethology proposes a theoretical concept being ‘the most recent attempt at explaining both animal and human behaviour. The concept is based on an assumption that behavioural patterns, similarly to morphological structures and physiological processes, are species-specific and related to a species phylogeny. Therefore ethology is rooted in the theory of biological evolution. Behavioural pattern emerges as a result of selective pressures of an environment thus ensuring to the highest possible degree survival of a species under given environmental conditions. Ome of the basic ethological ideas is distinction between inborn and acquired behaviour. Inborn behavioural pattern is formed by a „mechanism” of mutation and selection. Hence it emerges by the way of phylogenetic processes, while acquired behaviour is due to interactions between an individual and environment. Ethology has considerable accomplishments in explaining inborn behaviour. According to its concept such a behavioural pattern consists of four parts: apetention — search for «clue stimulators in environment, operation of relasing mechanism in response to occurrence of a clue stimulator, cours of action — a constant „rigid” sequence of movements executed by effectors (inherited coordination), calming down after the action. The author reconstructs three laws accepted by ethologists: the law of inborn behaviour, the law of learning and the law of protocultural behaviour. The first law is the basic one for ethology, the other two are its derivatives (concretizations). In lower animals (worms and lower forms) only inborn. behavioural patterns are present, later on there appears individual accumulation of information — learning. Phenomena of protoculture are mainly characteristic for birds and mammals, although its scope is limited. Protoculture consists of behaviours learned socially from other individuals of the same species. Human ethology occupies a separate position. Man, like other species, has acquired his properties on an evolutionary way. For instance, behaviour of infants is mainly determined by inborn factors, In adults inborn elements of behaviour occur as parts of particular actions (first of all sexual, aggressive and child care practices), Ethology also holds that potential for creation of (culture has arisen during anthropogenesis as a specific human adaptive function. Special place of man among living beings is related to the mew principle of evolution that is called the cultural evolution.